LOYALTY AS A PERSONAL REGULATOR STUDENT RELATIONSHIP - I.M. Svyrydenko (Academy of Cognitive and Natural Sciences, 2009)
The article dials with the main approaches to understanding the term fidelity in personal relations of student's. The content structure of this term is presented.